Hearing loss in the trenches – a hidden morbidity of World War I. Issue 11 (29th October 2018) - Conroy, K; Malik, V
Abstract: Background: One hundred years ago, millions of British and Allied troops were fighting in the trenches of the Great War. With a tenth of soldiers losing their lives, hearing loss seemed a low priority; however, vast numbers of troops sustained significant hearing loss. Method: A review was conducted of literature published between 1914 and 1925. Results: Soldiers were exposed to up to 185 dB of sustained noise from new, high-energy weapons, which caused 'labyrinthine concussion'. Traumatic injuries, non-organic hearing loss and malingering were also common. One source estimated that 2.4 per cent of the army was disabled by hearing loss. However, many British doctors viewed this 'soldier's deafness' as a temporary affliction, resulting in soldiers being labelled as malingerers or 'hysterical'. Conclusion: Today, one can recognise that a scant evidence base and misconceptions influenced the mismanagement of hearing loss by otolaryngologists in World War I. However, noise-induced hearing loss is still very much a feature of armed conflict.